High-throughput and low-overhead probabilistic routing based on multi-player bargaining game for opportunistic networks - Zhi REN; Jian-wei SUO; Wen-peng LIU; Hong-jiang LEI; Qian-bin CHEN (Tongxin xuebao)
To address the problems existing in the present probabilistic routing based on bargaining games,including unidirectional transmission of messages degrades the success ratio,depending on the virtual money decreases the purchasing power of nodes,and redundancy exists in the interaction process of messages,an routing algorithm based on multi-player bargaining game for opportunistic networks,HLPR-MG,was proposed.Through extending the two-player game to a multi-player bargaining game,introducing the barter trade to enhance purchasing power of nodes,and improving the existing interaction mechanism to reduce the times of game,proposed algorithm achieves the effect of increasing network throughput and decreasing control overhead.Theoretical analysis verifies the effectiveness of HLPR-MG,and simulation results show that HLPR-MG improves the network throughput and success ratio at least 3.63%,and reduces the control overhead and average end-to-end delay by more than 17.76% and 4.03%,respectively,as compared to the classical GSCP and BG algorithms.